Effects of Transplanted Heparin-Poloxamer Hydrogel Combining Dental Pulp Stem Cells and bFGF on Spinal Cord Injury Repair. (27th March 2018) - Luo, Lihua; Albashari, Abdullkhaleg Ali; Wang, Xiaoyan; Jin, Ling; Zhang, Yanni; Zheng, Lina; Xia, Jianjian; Xu, Helin; Zhao, Yingzheng; Xiao, Jian; He, Yan; Ye, Qingsong
Abstract : Spinal cord injury (SCI) is one of serious traumatic diseases of the central nervous system and has no effective treatment because of its complicated pathophysiology. Tissue engineering strategy which contains scaffolds, cells, and growth factors can provide a promising treatment for SCI. Hydrogel that has 3D network structure and biomimetic microenvironment can support cellular growth and embed biological macromolecules for sustaining release. Dental pulp stem cells (DPSCs), derived from cranial neural crest, possess mesenchymal stem cell (MSC) characteristics and have an ability to provide neuroprotective and neurotrophic properties for SCI treatment. Basic fibroblast growth factor (bFGF) is able to promote cell survival and proliferation and also has beneficial effect on neural regeneration and functional recovery after SCI. Herein, a thermosensitive heparin-poloxamer (HP) hydrogel containing DPSCs and bFGF was prepared, and the effects of HP-bFGF-DPSCs on neuron restoration after SCI were evaluated by functional recovery tests, western blotting, magnetic resonance imaging (MRI), histology evaluation, and immunohistochemistry. The results suggested that transplanted HP hydrogel containing DPSCs and bFGF had a significant impact on spinal cord repair and regeneration and may provide a promising strategy for neuron repair, functional recovery, and tissue regeneration after SCI.